Response of sesame (Sesamum indicum L.) to foliar-applied thiourea under saline conditions - Dhillon, Sadia Aziz; Mujahid, Nazoora; Shahbaz, Muhammad; Debez, Ahmed (International Journal of Applied and Experimental Biology, 2023)
Salt stress is among the most pervasive limitations for food production, which eventually results in negative financial, environmental and social consequences. Thiourea is a vital chemical which improves growth and yield of plants. Sesame (Sesamum indicum L.) is a crop of semi-arid and arid regions, whose medicinal and seed oil properties are well known. A pot experiment was carried out to examine the impact of thiourea on sesame plants exposed to saline conditions. Two cultivars of sesame, i.e., TH-5 and TH-6 were used. Two levels (0 and 70 mM) of salinity stress as well as two foliar-applied levels (water spray and 150 mM) of thiourea were maintained after 28 and 34 days of seed sowing, respectively. Data for various morphological and physiological attributes was taken after 56 days of seed sowing. The results showed that salinity stress diminished shoot mass along with root mass (fresh and dry) as well as shoot and root lengths. Of physiological parameters, chlorophyll and gas exchange attributes were also negatively affected by the salinity stress. Salinity stress escalated the activities of SOD and POD as well as the levels of MDA. Foliar-applied thiourea raised the contents of chlorophyll b, total chlorophyll and carotenoids of cv. TH-6 under salt stress. The activity of POD of both cultivars under control and salt stress conditions and root K+ concentration of cv.TH-5 under salt stress were also enhanced by thiourea. Overall, foliar application of thiourea mitigated the negative impacts of salinity on sesame.